Trichloranoids A–D, antimalarial sesquiterpenoid trimers from Chloranthus spicatus. Issue 8 (24th February 2021) - Zhou, Jun-Su; Liu, Qun-Fang; Zimbres, Flavia M.; Butler, Joshua H.; Cassera, Maria B.; Zhou, Bin; Yue, Jian-Min
Abstract : Four new anti-malarial sesquiterpenoid trimers including two rearranged skeletons were isolated from Chloranthus spicatus . The structurally different but biogenetically related compounds 1, 2 and 5 rationalized the biradical pathway, and vice versa . Abstract : Four new lindenane sesquiterpenoid trimers, designated as trichloranoids A–D (1–4 ), along with a known analogue (5 ) were isolated from Chloranthus spicatus . Their structures were elucidated by a combination of diverse methods, including DP4+ probability and TDDFT-ECD calculations. Compounds 1 and 2 incorporated one unprecedented skeletal unit respectively in their western hemisphere, and each of them was likely formed biogenetically via a biradical rearrangement of the vinylcyclopropane. Compounds 1, 4, and 5 exhibited moderate antimalarial activities.